Evaluating use of higher dose oxybutynin in combination with desmopressin for refractory nocturnal enuresis. Issue 4 (August 2016) - Berkenwald, Aaron; Pires, Jacqueline; Ellsworth, Pamela
Summary: Introduction: Nocturnal enuresis is a common pediatric condition with limited treatment options. In older children, pharmacologic therapy is often the preferred treatment. Pharmacologic therapies including desmopressin (DDAVP) or imipramine are effective in 40–50% of children. However, imipramine has serious safety concerns. Desmopressin in combination with a fixed dose anticholinergic has been shown to be useful in individuals who fail desmopressin monotherapy, but still fails to achieve success rates greater than 60%. Objective: The goal was to explore the efficacy and safety of using combination therapy desmopressin plus oxybutynin with increasing dose of oxybutynin in patients refractory to standard combination therapy. Study design: This was a single institution, IRB-approved, retrospective chart review of 61 patients (ages 7–18 years) including those with monosymptomatic primary nocturnal enuresis and non-monosymptomatic enuresis with controlled daytime voiding symptoms (CDVS) treated initially with desmopressin. All patients who failed initial therapy with desmopressin were started on combination therapy desmopressin (0.6 mg) plus standard dose (5 mg) oxybutynin. In patients who failed standard combination therapy, the dose of oxybutynin was titrated upwards until a response or the maximum dose of 10 mg was achieved. Demographic and medical history data were evaluated to determine predictive factors associated with response/failure to different therapy groups. Results: The use of escalating doses of oxybutynin in combination with desmopressin achieved an overall response rate of 96.7% defined as a 2-week period without any enuretic events following initiation of treatment. Low-dose combination therapy (LDCT) (0.6 mg of desmopressin + 5 mg of oxybutynin) had a response rate of 68% (Table). Advanced dose combination therapy (ADCT) (0.6 mg of desmopressin + 7.5–10 mg of oxybutynin) had a response rate of 75.0%. A statistically significant relationship was found correlating both attention deficit disorder/attention-deficit hyperactivity disorder(ADD/ADHD) and CDVS with failure on monotherapy. No patients in the study reported any adverse events or side effects from the medications. Discussion: The overall success rate of 96.7% with titrated doses of oxybutynin in combination with desmopressin is considerably higher than the response rates on fixed dose combination therapy quoted in the literature and supports the need for further evaluation in larger studies. Additionally, we found a statistically significant association between monotherapy failure and children with either ADD/ADHD or controlled daytime voiding symptoms. Our study is limited by small numbers and larger studies are needed to confirm these results. Conclusion: Our results suggest that ADCT is a safe and effective treatment option for primary nocturnal enuresis refractory to standard and low-dose combination therapy.   Desmopressin monotherapy LDCT ADCT Total Patients treated 61 25 8 61 Responders 36 17 6 59 Response rate 59.0% 68.0% 75.0% 96.7%